The Socio-economic Dimensions of the Fisherman’s Well-being at Batam Island: A Descriptive Survey - Isa, Khairunesa Binti; Palpanadan, Sarala Thulasi (International Journal of Psychosocial Rehabilitation, 2020)
The well-being of the people is a fundamental part of a government’s drive towards a developed nation. Indonesia’s maritime community is one of the few minority communities that need attention in order to achieve Indonesia’s balance of growth. Therefore, this study aims to achieve three main objectives, namely, to know the well-being of the Bertam Island fishermen, to explore the social and economic dimensions of Bertam Island and to study the role of the government in enhancing the wellbeing of the well-being of Bertam Island, Batam. This study is a descriptive survey study. The data were collected using survey method and questionnaire instrument. The study found that the well-being of the Bertam Island community is at a moderate level in terms of social and economic dimensions and the role of the government in enhancing fisheries welfare, which have mean score value 2.66, 2.60 and 2.55 respectively. Overall, the well-being of fishermen can be measured by the socio-economic dimensions and the role of government can be conducted from time to time and make well-being as one of the benchmarks in monitoring the current development of the Bertam Island, Batam.